Strength uncertainty analysis of composite turbine blade with small sample size. (October 2021) - Chen, Gaoxiang; Fan, Jiang; Dong, Shaojing; Liu, Daxiang
Abstract: SiC/SiC ceramic matrix composites (CMCs) exhibit significant randomness of damage processes under load. In this study, a simplified simulation method was established based on the macroscopic damage constitutive model, characteristics of fewer test samples, and complex data sources for determining the randomness of the material behavior. Moreover, the established model was verified by introducing an uncertainty parameter to the constitutive model. By considering a typical high-dimensional nonlinear function as a numerical example, the reliability and error of the characterization methods were compared with specimens and studied in terms of the extreme-value interval, tolerance interval, evidence theory, and fuzzy set method with the distribution characteristics of single and mixed parameters. In conjunction with the sensitivity analysis, the randomness of the mechanical behavior was more evident at the damage stage, and the uncertainty of material behavior relied on the loading state. In addition, the correction method of the constitutive parameters and formal errors of the model were established using the Bayesian theorem to acquire additional data. Thereafter, the proposed method was employed for quantifying the uncertainty in the strength of the CMC turbine rotor blade. The determinacy results revealed that the failure risk could be more effectively evaluated by the strength analysis considering the uncertainty of the model, thus providing guidance toward structural design improvement aligned with engineering practice.